Charlie, the lonesome cougar [videorecording (DVD)] - Hibler, Winston; Brown, Ron actor; Russell, Brian actor; Wallace, Linda (Walt Disney Entertainment : Distributed by Buena Vista Home Entertainment, 2004)
Lost, abandoned and frightened, a young cougar is discovered and "adopted" by a lumberman.